“Pasang”, Knowledge and Implementation of Local Wisdom in The Kajang Traditional Forest Area, South Sulawesi - Nurmala; Muh. Dassir; Supratman (Politeknik Pariwisata Makassar, Indonesia, 2022)
The Kajang tribe as a cultural and environmental tourism destination is a community of indigenous people who live in harmony with nature by having the life principle of